Microbial degradation of persistent organic pollutants in food supply chain - Pankaj Kumar; Ajay Singh; Manikant Tripathi; Deepti Diwan; R. Manimekalai; Minaxi Sharma; Sudisha Jogaiah; Ramesh Chandra Dubey; Gauri Dutt Sharma (Discover Food)
Abstract There are many environmental problems around us that can harm our health. Among them, environmental pollution, food contamination and adulteration, and antinutrients of foods are listed at the top. Persistent organic pollutants (POPs) are one of them that focus the attention of every researcher, industrialist, and policymaker due to their ill effects on animal and human populations nowadays. Industrialization is the main causative agent that has even put them as part of our food web. The severity of their impact can rely on their transportation across international boundaries. To date, about 26 pesticides have been identified under the POP category. These are toxic, persistent, and bioaccumulated among living beings, whereas polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) are as toxic as industrial effluents and also travel too long by way of air. Sometimes, they may be generated by unintentional means during various agricultural practices, too. Besides all these, food by way of processing, packaging, transportation, and storage could be aligned as potential sources for POP invasion in the food supply chain. There may be chances that POPs contaminate food through raw materials. The International Agency for Research on Cancer (IARC) of the World Health Organization (WHO) has identified some of them as a part of the "dirty dozen" due to their role in cancer development. The traditional methods to manage the POPs are neither efficient nor eco-friendly. The only sustainable way to break down POPs is the application of microorganisms. Keeping in mind the severity aspect, resistant to degradation and dangerous to living creatures of POPs. This review provides the insights and details of various extraction, detection and degradation techniques of POPs.